Intra‐annual patterns of coastal larval fish assemblages along environmental gradients in the northeastern Mediterranean. (27th December 2017) - Mavruk, Sinan; Bengil, Fethi; Yüksek, Ahsen; Özyurt, Caner Enver; Kiyağa, Volkan Barış; Avşar, Dursun
Abstract: To date, little is known about the larval‐fish assemblages (LFAs) in the eastern Mediterranean. The purpose of this study is to investigate the intra‐annual variations of LFAs with an emphasis on the effects of physical, chemical, biological and meteorological conditions in the gulf of Iskenderun, which is a shallow (100 m maximum depth), semi‐enclosed bay located in the northeastern corner of the Mediterranean. The gulf is under the influence of offshore waters throughout the year. The study was based on an ichthyoplankton survey program performed at 28 stations over 12 months, between November 2009 and October 2010. During the study, a total of 11, 411 larval individuals belonging to 177 taxa were sampled. The jackknife estimate of maximum species richness was 225 ± 19 for the study area. The maximum larval richness (84 species) and abundance (827 larvae/10 m 2 ) values coincided with spring bloom in April. Gobiids dominated the ichthyoplankton of Iskenderun Bay by constituting 9% of species richness and 42% of total individuals. Four LFAs were identified which were in early winter (November to January), late winter (February and March), spring (April to June) and summer (July to October). The intra‐annual variations of richness, abundance and composition of ichthyoplankton were significantly correlated with the temperature and mesozooplankton biomass. The wind conditions and thermal stratification were also significantly correlated with the composition of LFAs. In conclusion, phenology of LFAs were formed under the influence of physical and tropho‐dynamic conditions in Iskenderun Bay, Northeastern Mediterranean.